Synthesis, crystal growth, characterization and Hirshfeld surface analysis of 2-aminopyridinium 4-aminobenzoate single crystal for non linear optical applications. (23rd February 2019) - Indira, K.; Chitravel, T.; Saravanan, R. R.; Indumathi, P.
Abstract: The title compound, 2-aminopyridinium 4-aminobenzoate (2AP4AB) has been synthesised by the addition of 2-aminopyridine (C5 H6 N2 ) and 4-aminobenzoic acid (C7 H7 NO2 ) in stoichiometric ratio (1:1) using ethanol as solvent. The single crystal of 2AP4AB has been grown by solution growth slow evaporation technique. Single crystal XRD confirmed that the crystal belongs to the orthorhombic system with the Non-centrosymmetric space group Pca2 1 . Thermal studies revealed the thermal stability of grown crystal up to 138 °C. Hirshfeld surface analysis is used to discuss the evaluation of intermolecular interactions. The LDT and SHG study were carried out to explore the laser stability and the existence of NLO property in the 2AP4AB.